The democratic recession and its impact on business - Diamond, Larry (Henry Stewart Talks, 2021)
Democratic recession, Political rights, Civil liberties, Illiberal populism, Authoritarian populism, Competitive authoritarianism, Regulatory authority, Open market capitalism, Monopoly, Oligopoly, Intellectual property, Transparency, Corruption, Global business environment, Corporate responsibility, Labor rights